Sustainability Reporting and Corporate Social Responsibility: A Conceptual Review of Global ESG Standards - Aswanto Aswanto; Andi Cici Thania; Sahal Hanafi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study develops an integrative conceptual review of sustainability reporting and corporate social responsibility within the evolving architecture of global ESG standards. Drawing on a systematic and theory-driven synthesis of leading scholarship in accounting, management, and sustainability, the analysis examines three interconnected dimensions: theoretical foundations of ESG disclosure, institutional and regulatory dynamics, and performance implications. The review identifies persistent conceptual ambiguities between CSR and ESG, heterogeneous regulatory regimes, and conditional performance pathways moderated by governance quality and measurement coherence. By organizing the literature into an analytically unified framework, the study clarifies how global ESG standards translate normative responsibility into structured accountability mechanisms embedded within capital market infrastructures. The findings highlight that regulatory convergence, governance oversight, and strategic integration jointly determine whether ESG reporting enhances transparency and long-term value creation. The proposed conceptual model offers theoretical refinement and methodological guidance for future empirical research, contributing to debates on standard harmonization, disclosure credibility, and the role of sustainability reporting in contemporary economic governance.